PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITIES OF 70% ETHANOL EXTRACTS OF KALANGKALA SEEDS (Litsea angulata Bl.) ON BACTERIA CAUSES ACNEPropionibacterium acnes - Hafiz Ramadhan; Muhammad Arsyad; Putri Indah Sayakti (Borneo Journal of Pharmascientech, 2020)
Acne vulgaris or acne is a chronic inflammatory disease in the polysebaseus unit that often occurs especially in teenagers and adults, one of which is caused by the bacterium Propionibacterium acnes. Natural material that has the potential as an antibacterial is Kalangkala (Litsea angulata Bl.), where some people in South Kalimantan use the seeds to treat boils. This research purposes to determine the content of secondary metabolites of 70% ethanol extract of Kalangkala seeds andtheir activities as antibacterial againts P.acnes. The phytochemical screening test includes flavonoids, alkaloids, saponins, steroids-terpenoids and tannins. The method of testing the antibacterial activity with the well diffusion method using extract concentration 100%; 50%; 25%; 12.5%; 6.25%; and 3.125%. The results showed 70% ethanol extract of Kalangkala seeds containing flavonoids, alkaloids, saponins and tannins. The antibacterial activity of 70% ethanol extract of Kalangkala seeds againts Propionibacterium acnes bacteria with well diffusion method was obtained by MIC that is 25% with an average inhibition zone diameter of 8,667 mm which included the moderate category as an antibacterial agent.